From family to university: Best practices for inclusive tertiary education - Baider, Fabienne; Karpava, Sviatlana (Glottodidactica, 2023)
This article investigates practices and integration strategies implemented by a European network of universities with regard to refugees and international students, in particular, integration practices at two levels: governance and policies, regarding the institutional initiatives used and their relative success; second, the experience of such policies by international students. Our study revealed that in relation to refugee integration there is an overall lack of organisation, with too little, scattered information with respect to a bottom-up policy. In contrast, with regard to international students the system works fairly well, due to the top-down policy promoted by the EU. We propose that the EU put in place a specific program for refugee integration, such as ERASMUS+, focused on strengthening links with refugee families and schools with a high proportion of refugees.